2016
DOI: 10.3892/mmr.2016.6094
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activators suppress breast cancer cell growth by inhibiting DVL3-facilitated Wnt/β-catenin signaling pathway activity

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is a principal regulator of metabolism and the conservation of energy in cells, and protects them from exposure to various stressors. AMPK activators may exhibit therapeutic potential as suppressors of cell growth; however, the molecular mechanism underlying this phenomenon in various cancer cells remains to be fully elucidated. The present study investigated the effects of AMPK activators on breast cancer cell growth and specified the underlying molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
(53 reference statements)
1
34
2
Order By: Relevance
“…In general, activation of AMPK acts as a sensor of energy status and a mediator of energy homeostasis; therefore, it is possible that IM‐mediated suppression of glycolysis disturbs the intracellular energy balance and activates AMPK. Several studies suggest that inhibiting the mTORC1 and Wnt/β‐catenin signaling pathways, which act downstream of AMPK activation, has anti‐cancer effects . There is little information about the relationship between AMPK and TKI, but we assume that activating AMPK by continuous exposure to IM might increase sensitivity to TKI by affecting the above signaling pathways.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, activation of AMPK acts as a sensor of energy status and a mediator of energy homeostasis; therefore, it is possible that IM‐mediated suppression of glycolysis disturbs the intracellular energy balance and activates AMPK. Several studies suggest that inhibiting the mTORC1 and Wnt/β‐catenin signaling pathways, which act downstream of AMPK activation, has anti‐cancer effects . There is little information about the relationship between AMPK and TKI, but we assume that activating AMPK by continuous exposure to IM might increase sensitivity to TKI by affecting the above signaling pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggest that inhibiting the mTORC1 and Wnt/b-catenin signaling pathways, which act downstream of AMPK activation, has anti-cancer effects. 41,42 There is little information about the relationship between AMPK and TKI, but we assume that activating AMPK by continuous exposure to IM might increase sensitivity to TKI by affecting the above signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…FZD/LRP receptors together with DVL are intrinsic key players in the Wnt/β-catenin pathway. Studies have shown that alteration of these targets regulates the pathway activity in cancers including HCC [ 13 , 31 , 40 ]. Overexpression of these targets serves to activate Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Targets of curcumin in Wnt/β-catenin signaling. Wnts are a family of secreted glycoproteins that regulate multiple signaling pathways through β-catenin-dependent and -independent mechanisms (65)(66)(67). Wnts serve a crucial role in development, survival and metabolism.…”
Section: Targets Of Curcumin In Ras Signalingmentioning
confidence: 99%